A Distributed Leadership Perspective for Critical Consciousness in Middle Grades - Kenneth M Bond; Daniel P Tulino (Middle Grades Review, 2023)
In middle-grades settings, students are cultivating critical consciousness to apply general knowledge of equity to their local context(s) (Nojan, 2020). As educators work to foster environments that allow middle-grade students to cultivate critical consciousness, expectations have shifted in the area of leading for equity. We have outlined a leadership framework we believe will advance the collective critical consciousness with examples for middle-grade contexts. Our focus is working toward equitable outcomes through one’s sociopolitical development and creating ways to further the collective critical consciousness of the entire school community through a distributed leadership perspective. Through this lens, our hope is to outline how educational leaders may develop their critical consciousness in the context of their priorities as well as work towards a shared sense of critical consciousness and sociopolitical action in the classrooms, schools, districts, and the wider community.
Keywords: Equity; Social Justice; Critical Consciousness; Distributed Leadership